Financial Value, Strategic Value And Macroeconomic Value Bank Shariah Di Indonesia - Wijayati, Fitri Laela; Melinda, Dita (BISNIS, 2017)
The purpose of this study is to indentified drivers that have relationship with performance value in Indonesian Sharia Bank as an alternative to measure syariah bank performace. This study try to gived an alternative measurement sharia bank’s performance based on internal aspect and eksternal aspect which are may haved been relationship in sharia bank performance. The sample of this study is Indonesian sharia bank which used panel data in periode 2010-2015. This study found there is relationship between financial,strategic value and macroeconomy have relationship to sharia bank performance and only zakat Performance ratio and Sohibul Maal Welfare Ratio have significant relationship with sharia bank performance